Phytolacca yunnanensis (Phytolaccaceae), a new species from China with distinctive inflorescence characteristics - Li, Xin-Hua; Zhou, Wen; Guo, Jia-Cheng; Yin, Xiao-Ming (Phytotaxa, 2020)
Phytolacca yunnanensis is described and illustrated as a new species from Yunnan Province, China. This new species is characterized by the distinctive dense translucent multicellular trichomes along the peduncles, raches, and pedicels of both racemose inflorescences and infructescences. These translucent multicellular trichomes, which were revealed by using stereomicroscope and SEM, represents the first discovery in the genus Phytolacca. P. yunnanensis resembles P. acinosa in sharing the free carpels, but differs by the 4-5-carpellate gynoecia. P. yunnanensis is also similar to P. exiensis by the number of carpels, but can be easily distinguished from the latter in having free carpels.